(4x+1)(3x-7)-2(6x+5)=0

Simple and best practice solution for (4x+1)(3x-7)-2(6x+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+1)(3x-7)-2(6x+5)=0 equation:



(4x+1)(3x-7)-2(6x+5)=0
We multiply parentheses
(4x+1)(3x-7)-12x-10=0
We multiply parentheses ..
(+12x^2-28x+3x-7)-12x-10=0
We get rid of parentheses
12x^2-28x+3x-12x-7-10=0
We add all the numbers together, and all the variables
12x^2-37x-17=0
a = 12; b = -37; c = -17;
Δ = b2-4ac
Δ = -372-4·12·(-17)
Δ = 2185
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-37)-\sqrt{2185}}{2*12}=\frac{37-\sqrt{2185}}{24} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-37)+\sqrt{2185}}{2*12}=\frac{37+\sqrt{2185}}{24} $

See similar equations:

| 3-2x+7-3x=6+4x+14+6x | | 4(3p+2)-5(6p-1)=2(p-8)-6(7p-4)+4p | | 2x(-5)+3=29-4x | | 3x+1÷2x-2=7 | | 15(a-4)-2(a-9)+5(a+6)=0 | | 3x+1÷2x2=7 | | 1/11y-4=-9 | | 8^x*16^x=4^72-x | | 3x-6-9x=-x+8 | | 3x+42+9x-6=180 | | -x-2x-1=3x+4+1= | | 3x+3=3x+14 | | 3/5x+6=13 | | 2x3+6x=15x2-7 | | 2^2x+2^2x+1-8=0 | | X/3=(2+x)/4 | | 2y+3=21-4y | | 2x-5+(8/x)=0 | | 2x+6=7x14 | | 6x8=x | | -2x²+5x-3=0 | | 3^3x+2=243 | | 5-2=-5x/2 | | 2-(3x-7/4)+x+17/5=0 | | 21–x=4x. | | 1-2x/5=2-x/2 | | 4D^4+4D^3-3D^2-2D+1)y=0 | | -27/x+0.5x+1.5=0 | | x2+15x-56.25=0 | | x2-7x-34=10 | | 11m-6m=30 | | 10x-6x2=0 |

Equations solver categories